Correlative light and electron microscopy IV - Muller-Reichert, Thomas; Verkade, Paul (Methods in cell biology, 2021)
Abstract: Correlative light and electron microscopy (CLEM) combines the strengths of light microscopy (LM) and electron microscopy (EM) to pin-point and visualize cellular or macromolecular structures. However, there are many different imaging modalities that can be combined in a CLEM workflow, creating a vast number of combinations that can overwhelm new-comers to the field. Here, we offer a conceptual framework to help guide the decision-making process for choosing the CLEM workflow that can best address your research question, based on the answer to five questions.